2021
DOI: 10.1186/s12870-021-03211-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of pollen limitation, floral traits and pollinators on reproductive success of Hedysarum scoparium Fisch. et Mey. in different habitats

Abstract: Background Reproduction in most flowering plants may be limited because of the decreased visitation or activity of pollinators in fragmented habitats. Hedysarum scoparium Fisch. et Mey. is an arid region shrub with ecological importance. We explored the pollen limitation and seed set of Hedysarum scoparium in fragmented and restored environments, and examined whether pollen limitation is a significant limiting factor for seed set. We also compared floral traits and pollinator visitation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Effective pollinators spent more time in open flowers and visited regions with greater resources [36,37]. A similar study suggested that the number of open flowers was positively correlated with fruit and seed production [38].…”
Section: Plant Pollination Efficiency Under Different Grazing Intensi...mentioning
confidence: 88%
“…Effective pollinators spent more time in open flowers and visited regions with greater resources [36,37]. A similar study suggested that the number of open flowers was positively correlated with fruit and seed production [38].…”
Section: Plant Pollination Efficiency Under Different Grazing Intensi...mentioning
confidence: 88%